The Practice of Extensive Reading among EFL Learners in Tertiary Level - Martina, Feny; Syafryadin, Syafryadin; Utama, Jeka Agustia (Yavana Bhasha : Journal of English Language Education, 2020)
Students had some problems in terms of extensive reading. The problems were (1) students forget some principles and benefits of extensive reading because they learned about principle and benefits of extensive reading in the previous semester, (2) students do not know how to implement a successful practice of extensive reading, and (3) students were still difficult to enjoy and get information in their reading of either fiction or nonfiction books. Thus, this research was aimed to know how students implement extensive reading and students’ difficulties when practice extensive reading. This research was qualitative descriptive research. The subject of this research was the fourth-semester students in the English Education Study Program of Institut Agama Islam Negeri Bengkulu. The instruments of this research were observation checklist, interview sheet, and documentation. The result of this research showed that there were students who implemented extensive reading but students implemented extensive reading in the outside classroom and the students still had difficulties when implementing extensive reading. The percentage of students’ implementation of extensive reading in the outside classroom was 62% while the percentage of students’ difficulties encounter practicing extensive reading was 91%. It concluded that students implemented extensive reading in the outside classroom without the supervision of the lecturer and students have many problems when practice extensive reading.